Translation of mRNAs with degenerate initiation triplet AUU displays high initiation factor 2 dependence and is subject to initiation factor 3 repression. - La Teana, A (1993)
The influence of the rare initiation triplet AUU on mRNA translation was investigated by comparing the activity of two pairs of model mRNAs that differ in the length of Shine-Dalgarno and spacer sequences. Irrespective of the initiation triplet (AUG or AUU), all mRNAs had similar template activity in vitro, but translation of AUU mRNAs depended more on initiation factor (IF) 2 and less on IF3 than that of AUG mRNAs. Increasing the IF3/ribosome ratio from 2 to 10 progressively inhibited the AUU mRNAs and abolished their capacity to compete for translating ribosomes with other mRNAs but did not affect activity of the AUG mRNAs. The effects induced by IF3 are from its different influence on on- and off-rates of the transition 30S preinitiation complex<==>30S initiation complex; depending on the nature of the initiation triplet (AUG or AUU) of the mRNA, IF3 shifts the position of equilibrium toward binding or dissociation of fMet-tRNA, respectively. Stimulation of fMet-tRNA binding and dissociation yields superimposable IF3 titration curves that saturate at an IF3/30S ratio of approximately 1, indicating that the data are from the interaction of one molecule of IF3 with the same 30S binding site. Both effects are either lost or strongly reduced with 30S mutants defective in IF3 binding. Translational repression of AUU mRNAs by IF3 is from the factor-dependent dissociation of fMet-tRNA from 30S subunits, which becomes relevant when excess IF3 interferes with the formation of 70S initiation complex, presumably by interacting with 50S subunit.